A fast multispectral diffuse optical tomography system for in vivo three-dimensional imaging of seizure dynamics - Yang, Jianjun (2012)
We describe a multispectral continuous-wave diffuse optical tomography (DOT) system that can be used for in vivo three-dimensional (3-D) imaging of seizure dynamics. Fast 3-D data acquisition is realized through a time multiplexing approach based on a parallel lighting configuration - our system can achieve 0.12ms per source per wavelength and up to 14Hz sampling rate for a full set of data for 3-D DOT image reconstruction. The system is validated using both static and dynamic tissue-like phantoms. An initial in vivo experiment using a rat model of seizure is also demonstrated.